(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article examines the Draft of Qanun Aceh on Family Law (Ahwal Al-Syakhsiyyah), focusing on its Islamic legal foundations, contextual adaptation in Aceh, and implications for family law practices. It addresses the research questions: (1) What are the key legal elements of the Qanun? (2) How does the Qanun align with national and Islamic legal principles? Employing normative juridical analysis, the study reveals the Qanun’s role in harmonizing Islamic principles with local customs while addressing gaps in existing national laws. Key findings highlight the Qanun’s provisions on marriage, divorce, inheritance, and child protection, offering a localized yet comprehensive legal framework